CO2 Reforming of Methane over Ni-0/La2O3 Catalyst Without Reduction Step: Effect of Calcination Atmosphere - Yang, Eun-hyeok; Moon, Dong Ju (SPRINGER/PLENUM PUBLISHERS, 2017)
La-Ni precursor prepared by EDTA-cellulose method was calcined under different atmosphere (Air or Ar), and the catalysts were characterized by various techniques. In this study, the possibility of reduction free catalyst for dry reforming of methane was investigated as well. It was observed that LaNiO3 perovskite structure was formed under the calcination of Air atmosphere, while Ni-0/La2O3-C structure was obtained under the calcination of Ar atmosphere due to the reducing and the oxidizing agents generated by the decomposition of organic species under inert atmosphere. It was found that even if LaNiO3-Ar had much larger size of nickel particle than LaNiO3-Air, the remained carbon species derived positive effect: the interfacial area among carbon, La2O3 and Ni-0 could lead to synergetic sites such as basic sites, which enhanced resistance to carbon deposition. Furthermore, the higher CH4 activation energy and basicity of LaNiO3-Ar catalyst might ascribe to equilibrium between CH4 decomposition and CO2 gasification rates. Thus, it is suggested that remained carbon species in Ar calcined catalyst did not negatively affect the catalytic activity, but it affected stability positively.
Keywords: NANOSTRUCTURED METALLIC CATALYSTS; IMPREGNATION COMBUSTION METHOD; PARTICLE-SIZE; PEROVSKITE CATALYSTS; CARBON NANOTUBES; DRY; NI; NICKEL; PERFORMANCE; GAS